Spinal neuron-glial crosstalk and ion channel dysregulation in diabetic neuropathic pain - Wu, Jie; Hu, Haijun; Li, Xi (Frontiers in Immunology, 2025)
Diabetic neuropathic pain (DNP) is one of the most prevalent complications of diabetes, characterized by a high global prevalence and a substantial affected population with limited effective therapeutic options. Although DNP is closely associated with hyperglycemia, an increasing body of research suggests that elevated blood glucose levels are not the sole inducers of DNP. The pathogenesis of DNP is intricate, involving the release of inflammatory mediators, alterations in synaptic plasticity, demyelination of nerve fibers, and ectopic impulse generation, yet the precise mechanisms remain to be elucidated. The spinal dorsal horn coordinates dynamic interactions between peripheral and central pain pathways, wherein dorsal horn neurons, microglia, and astrocytes synergize with Schwann cell-derived signals to process nociceptive information flow. Abnormally activated neurons can alter signal transduction by modifying the local microenvironment, compromising myelin integrity, and diminishing trophic support, leading to neuronal sensitization and an amplifying effect on peripheral pain signals, which in turn triggers neuropathic pain. Ion channels play a pivotal role in signal conduction, with the modulation of sodium, potassium, and calcium channels being particularly crucial for the regulation of pain signals. In light of the rising incidence of diabetes and the current scarcity of effective DNP treatments, a thorough investigation into the interactions between neurons and glial cells, especially the mechanisms of ion channel function in DNP, is imperative for identifying potential drug targets, developing novel therapeutic strategies, and thereby enhancing the prospects for DNP management.